Duck at the door - Urbanovic, Jackie (New York : HarperCollins, 2007)
When Max the duck decides to stay behind when his flock flies south, Irene invites him to stay with her for the winter.
1.6
K-3
Keywords: Ducks -- Fiction; Pets -- Fiction; Ducks -- Fiction; Pets -- Fiction